Candida albicans PROTEIN PROFILE CHANGES IN RESPONSE TO THE BUTANOLIC EXTRACT OF Sapindus saponariaL. - FIORINI, Adriana; ROSADO, Fabio Rogério; BETTEGA, Eliane Martins da Silva; MELO, Kátia Cristina Sibin; KUKOLJ, Caroline; BONFIM-MENDONÇA, Patrícia de Souza; SHINOBU-MESQUITA, Cristiane Suemi; GHIRALDI, Luciana Dias; CAMPANERUT, Paula Aline Zanetti; CAPOCI, Isis Regina Grenier; GODOY, Janine Silva Ribeiro; FERREIRA, Izabel Cristina Piloto; et al. (Revista do Instituto de Medicina Tropical de São Paulo, 2016)
Candida albicans is an opportunistic human pathogen that is capable of causing superficial and systemic infections in immunocompromised patients. Extracts of Sapindus saponaria have been used as antimicrobial agents against various organisms. In the present study, we used a combination of two-dimensional polyacrylamide gel electrophoresis (2D-PAGE) and matrix-assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF MS) to identify the changes in protein abundance of C. albicans after exposure to the minimal inhibitory concentration (MIC) and sub-minimal inhibitory concentration (sub-MIC) of the butanolic extract (BUTE) of S. saponaria and also to fluconazole. A total of six different proteins with greater than 1.5 fold induction or repression relative to the untreated control cells were identified among the three treatments. In general, proteins/enzymes involved with the glycolysis (GPM1, ENO1, FBA1), amino acid metabolism (ILV5, PDC11) and protein synthesis (ASC1) pathways were detected. In conclusion, our findings reveal antifungal-induced changes in protein abundance of C. albicans. By using the previously identified components of the BUTE of S. saponaria(e.g., saponins and sesquiterpene oligoglycosides), it will be possible to compare the behavior of compounds with unknown mechanisms of action, and this knowledge will help to focus the subsequent biochemical work aimed at defining the effects of these compounds.